Musikk og religion Tekster om musikk i religion og religion i musikk - Socanski Celik, Kristina (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2022)
Music plays an important role in many religions and in a variety of religious contexts. Music and Religion: Texts on Music in Religion and Religion in Music takes a look at the intersections between music and religion. We experience religion in music, and in religion we encounter musical expression. Although music and religion are unquestionably mutually pervasive, we can also come across gaps between them: Is it possible to move beyond a musical experience toward a religious one without having to hop over this gap? And is there any direct route from religion into music as an acoustic phenomenon? Without a religious interpretation of the music remaining? There is a wealth of research about music and religion, but little on how they meet. That is what this anthology seeks to remedy. Music and Religion will be relevant for anyone with an interest in encounters between these two phenomena. It will be especially relevant for students in performing, composing and scientific music education, as well as theology and religious studies. The anthology has been edited by Henrik Holm (associate professor in education at Oslo Metropolitan University and professor in philosophy at Rudolf Steiner University College) and Øivind Varkøy (professor in music education and music sciences at the Norwegian Academy of Music and professor II in music at Oslo Metropolitan University).